Update on clinical significance of coagulase-negative staphylococci. - Kloos, W E (1994)
The clinical significance of coagulase-negative Staphylococcus species (CNS) continues to increase as strategies in medical practice lead to more invasive procedures. Hospitalized patients that are immunocompromised and/or suffering from chronic diseases are the most vulnerable to infection. Since CNS are widespread on the human body and are capable of producing very large populations, distinguishing the etiologic agent(s) from contaminating flora is a serious challenge. For this reason, culture identification should proceed to the species and strain levels. A much stronger case can be made for the identification of a CNS etiologic agent if the same strain is repeatedly isolated from a series of specimens as opposed to the isolation of different strains of one or more species. Strain identity initially can be based on colony morphology, and then one or more molecular approaches can be used to gain information on the genotype. Many of the CNS species are commonly resistant to antibiotics that are being indicated for staphylococcal infections, with the exception of vancomycin. The widespread use of antibiotics in hospitals has provided a reservoir of antibiotic-resistant genes. The main focus on mechanisms of pathogenesis has been with foreign body infections and the role of specific adhesins and slime produced by Staphylococcus epidermidis. Slime can reduce the immune response and opsonophagocytosis, thereby interfering with host defense mechanisms. As we become more aware of the various strategies used by CNS, we will be in a better position to compromise their defense mechanisms and improve treatment.